ANALISIS LEARNING OBSTACLE MATA KULIAH KALKULUS PADA MAHASISWA IKIP SILIWANGI - Yuspriyati, Devi Nurul; Yuliani, Anik; Fitrianna, Aflich Yusnita (JURNAL e-DuMath, 2019)
Calculus is one of the subjects that must be taken by students majoring in mathematics education at the Teachers' Training College Siliwangi, this course is given to students in semester 4. From the analysis of learning obstacle, it can be seen that almost all mahsaiswa have difficulty learning in a calculus course. This is because the factors that influence in solving the problems given by the researchers. From the test results can also be seen the answer given by many students who make mistakes, be it in using formulas, operating, to answer directly without a process and students can not memjawab about a given test. These difficulties lead to poor results. It can be concluded that mahsiwa not been able to understand the material given or students only attend learning without any understanding of the material provided.